Designing mechanisms to encourage immigrants for official employment in Ukraine - Kostennikov, Dmytro (Pressing Problems of Public Administration, 2023)
This article offers an original perspective on the issue of incentivizing immigrants for official employment in Ukraine to support post-war reconstruction efforts. The proposed solution is viewed from the perspective of motivation and the organization within host communities. It’s evident that post-war Ukraine will require non-standard regulatory measures, as all neighboring countries are implementing similar strategies. This article aims to substantiate the organizational integration and motivational mechanisms for encouraging immigrants to engage in official employment in Ukraine as an urgent and strategically significant tool for implementing state immigration policy. The conclusion is drawn that in the context of intensified European integration efforts, we must also focus on areas beyond legislation. This includes education, employment opportunities, the establishment and operation of foreign companies in Ukraine, and attracting foreign workers through mechanisms such as language barrier improvement, recognition of foreign qualifications, skills enhancement, and improvements in social security and guarantees. Specifically, we should intensify: (a) development of attractive investment programs and financial incentives to attract Ukrainian expatriates and highly skilled immigrants to participate in Ukraine’s recovery and development projects after the war; (b) creation of specialized legal and tax conditions for immigrants wishing to contribute to the development of critical sectors such as infrastructure, education, healthcare, and innovation; (c) accreditation and recognition programs for foreign qualifications and experience to facilitate immigrant integration into Ukrainian professional unions and civil organizations; (d) partnerships with Ukrainian and international companies to create jobs and support immigrants in adapting to the Ukrainian job market and way of life; (e) development of programs for immigrant families wishing to join Ukrainian society, including educational and medical services for children and other support to create a favorable environment for resettles. Unfortunately, discussing the foreign-qualified labor force policy in the near future is challenging due to the security situation across our nation caused by the ongoing state of war. Therefore, migration policy’s primary focus is working with domestic resources to prevent their outflow.